2012
DOI: 10.2514/1.j051473
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds-Averaged Navier-Stokes Simulations of the HyShot II Scramjet

Abstract: The internal flow in the HyShot II scramjet is investigated through numerical simulations. A computational infrastructure to solve the compressible Reynolds-averaged Navier-Stokes equations on unstructured meshes is introduced. A combustion model based on tabulated chemistry is considered to incorporate detailed chemicalkinetics mechanics while retaining a low computational cost. Both nonreactive and reactive simulations have been performed, and results are compared with ground test measurements obtained at DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 54 publications
2
57
0
Order By: Relevance
“…More importantly, in a mixing-controlled flow, details of the combustion model have less influence on the solution. The relative agreement between the computed pressure profiles by Karl et al [19] and Pecnik et al [21] (two studies which used very different turbulent combustion models) is consistent with this.…”
Section: The Hyshot II Scramjetsupporting
confidence: 85%
See 4 more Smart Citations
“…More importantly, in a mixing-controlled flow, details of the combustion model have less influence on the solution. The relative agreement between the computed pressure profiles by Karl et al [19] and Pecnik et al [21] (two studies which used very different turbulent combustion models) is consistent with this.…”
Section: The Hyshot II Scramjetsupporting
confidence: 85%
“…Thus the computational domain is 1/4 of the width of the full combustor, with periodic boundary conditions used in the spanwise direction. This approximation was investigated by Pecnik et al [21] using RANS, and was found to be reasonable.…”
Section: Domains and Inflow Conditionsmentioning
confidence: 90%
See 3 more Smart Citations